On the Selection of High-z Quasars Using LOFAR Observations - Retana-Montenegro, Edwin; Röttgering, Huub (Frontiers in Astronomy and Space Sciences, 2018)
We present a method to identify candidate quasars which combines optical/infrared color selection with radio detections from the Low Frequency ARray (LOFAR) at 150MHz. We apply this {method} in a region of 9 square degrees located in the Boötes field, with a wealth of multi-wavelength data. Our LOFAR imaging in the central region reaches a rms noise of $\sim50μ$Jy with a resolution of $5''$. This is so deep that we also routinely, `radio-quiet' quasars. We use quasar spectroscopy from the literature to calculate the completeness and efficiency of our selection method. We conduct our analysis in two redshift intervals, $1<z<2$ and $2<z<3$. For objects at $1.0<z<2.0$, we identify $51%$ of the spectroscopic quasars, and $80%$ of our candidates are in the spectroscopic sample; while for objects at $2.0<z<3.0$ these numbers are $62%$ and $30%$, respectively. We investigate the effect of the radio spectral index distribution on our selection of candidate quasars. For this purpose, we calculate the spectral index between 1400MHz and 150MHz, by combining our LOFAR-Boötes data with 1.4GHz imaging of the Boötes field obtained with the Westerbork Synthesis Radio Telescope (WSRT), which has a rms noise of $σ\sim28μ$Jy with a resolution of $13''×27''$. We find that $27%$ of the candidate quasars are detected at 1400 MHz, and that these detected objects have a spectral index distribution with a median value of $α=-0.73±0.07$. Using a flux density threshold of $S_{150MHz}=1.50$mJy, so that all the $α>-1.0$ sources can be detected in the WSRT-Boötes map, we find that the spectral index distribution of the 21 quasars in the resulting sample is steeper than the general LOFAR-WSRT spectral index distribution with a median of $α=-0.80±0.06$. As the upcoming LOFAR wide area surveys are much deeper than the traditional 1.4GHz surveys like NVSS and FIRST, this indicates that LOFAR in combination with optical and infrared will be an excellent fishing ground to obtain large samples of quasars.